Visitors’ Perception and their Experience of Public Open Space of Bhadrakali Premises in Pokhara, Kaski, Nepal - Pokharel, Ramjee Prasad (Janapriya Journal of Interdisciplinary Studies, 2020)
The purpose of this study is to examine the users’ perception towards the existing management of public open space (POS) because urban public open space is the significant part of urban landscape. POSs are indispensable as it provides wellbeing, beautify the city and enhance quality of urban life so this case study is related to users’ perception about Bhadrakali premises as POS in Pokhara metropolitan city. Exploratory and prediction research design is followed and users’ experiences are analyzed on the basis of different groups of visitors inside the study area. It focuses on visitor’s perception towards attributes like condition of open space and the situation of infrastructure facilities there. The perception of visitor is scanned through filled up closed questionnaire form to express their perception with eight independent parameters such as accessibility, natural attraction, cultural heritage, safety, sanitation, parking facilities, internal layout and surrounding situation in the study area. The mapping process have been done with the help of ArcGIS. The statistical test revealed that there is a strong statistically significant association between the level of perception with the age, gender, caste, occupation and education status of visitors. The relationship between visitors and existing environment of Bhadrakali site play a significant role to understand visitor’s perception which supports in improving places according to their requirement. It is assumed that, positive perceptional indicators refer the popularity and well sophistication of public open space while negative indicators of visitors provide feedback for further space development and proper management of public open spaces.